2016
DOI: 10.1016/j.shaw.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Separate and Joint Associations of Shift Work and Sleep Quality with Lipids

Abstract: BackgroundShift work and/or sleep quality may affect health. We investigated whether shift work and sleep quality, separately and jointly, were associated with abnormal levels of triglycerides, total cholesterol (TC), and low-and high-density lipoprotein cholesterol in 360 police officers (27.5% women).MethodsTriglycerides, TC, and high-density lipoprotein were analyzed on the Abbott Architect; low-density lipoprotein was calculated. Shift work was assessed using City of Buffalo payroll work history records. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
8
0
3
Order By: Relevance
“…We included 46 studies [10,17,23,24,37,38,40,41,43,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]62,[65][66][67][68][69][70][71][73][74][75][76][77][78][79][80][81][82][83][84][85][86]91]. The overall SMD was − 0.08 (95CI − 0.12 to − 0.03; p = 0.001) with an important heterogeneity (I 2 = 85.9%) ( Fig.…”
Section: Meta-analysis Of Hdl Cholesterol For Each Type Of Shift Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 46 studies [10,17,23,24,37,38,40,41,43,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]62,[65][66][67][68][69][70][71][73][74][75][76][77][78][79][80][81][82][83][84][85][86]91]. The overall SMD was − 0.08 (95CI − 0.12 to − 0.03; p = 0.001) with an important heterogeneity (I 2 = 85.9%) ( Fig.…”
Section: Meta-analysis Of Hdl Cholesterol For Each Type Of Shift Workmentioning
confidence: 99%
“…2 and Supplementary Data 9). Among the 46 included studies, 6 studies reported permanent night shift [41,58,67,69,71,82] 43,45,49,62,67,68,75,79,81,84]. We found a significantly lower blood level of c-HDL among permanent night shift workers (SMD = − 0.16; 95CI − 0.32 to 0.00; p = 0.05; I 2 = 72.3%), rotating 3 × 8 shift workers (− 0.10; 95CI − 0.17 to − 0.02; p = 0.018; I 2 = 78.8%), and non-specified shift workers (− 0.08; 95CI − 0.15 to − 0.01; p = 0.027; I 2 = 81.7%).…”
Section: Meta-analysis Of Hdl Cholesterol For Each Type Of Shift Workmentioning
confidence: 99%
“…prevalence of MetS in MPO with ≥10 years at the PMESP. These findings suggest that the job characteristics of police officers, including excessive work hours, restricted night sleep due to the shift work schedule, potential and unexpected stressor situations (Charles et al, 2016;de Souza et al, 2018;Esquirol et al, 2009;Violanti et al, 2017), and low physical activity during work (Porto et al, 2020 unpublished data) contribute to the development of MetS. It is also important to point out that aging per se also plays an essential role in MetS development because there is a high occurrence of chronic diseases in the aged population (Schmidt et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown high levels of TG more prevalent in night shift workers with no difference in serum HDL level. [ 18 ] Sleep quality and its influence in shift work play a role in the alteration of some lipid parameters[ 19 ] But some studies found no such difference for triglyceride and HDL between day and night shift work. [ 20 ] Lipid metabolism is susceptible to the effects of irregular shift work schedules and deranged sleep.…”
Section: Discussionmentioning
confidence: 99%